Analysing kinematics of a novel 3CPS parallel manipulator based on Rodrigues parameters - Cheng, Gang (Strojniški vestnik, 2013)
In order to adjust the poses of the segment mirrors and give the correct surface shape to a large aperture telescope, an active adjusting platform for segment mirror with a novel 3CPS parallel manipulator as core module is proposed. The platform has 6 degree-of-freedoms (DOFs) including three translational freedoms and three rotational freedoms. Its kinematics are analysed systematically. By means of the Rodrigues parameters method, the formulae for solving the inverse/forward displacement, the inverse/forward velocity, and the inverse/ forward acceleration kinematics are derived. A numerical simulation of the kinematics model is then carried out combining the topological structure characteristics of the manipulator. The correctness of the kinematics model is verified by an experiment in which the pose of moving platform is measured using a photogrammetric method.
Keywords: 3CPS parallel manipulator; active adjusting platform; aktivna nastavitvena platforma; astronomski teleskopi; fotogrametrija; kinematics; kinematika; paralelni manipulatorji; photogrammetry; Rodrigues parameters; Rodriguesovi parametri; segmentna zrcala; telescopes